2015
DOI: 10.1136/bmjqs-2015-004116
|View full text |Cite
|
Sign up to set email alerts
|

The SQUIRE Guidelines: an evaluation from the field, 5 years post release

Abstract: BackgroundThe Standards for Quality Improvement Reporting Excellence (SQUIRE) Guidelines were published in 2008 to increase the completeness, precision and accuracy of published reports of systematic efforts to improve the quality, value and safety of healthcare. Since that time, the field has expanded. We asked people from the field to evaluate the Guidelines, a novel approach to a first step in revision.MethodsEvaluative design using focus groups and semi-structured interviews with 29 end users and an adviso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 13 publications
1
47
0
4
Order By: Relevance
“…19 Semistructured interviews and focus groups with 29 end-users of SQUIRE 1.0 revealed that many found SQUIRE 1.0 helpful in planning and doing improvement work, but less so in the writing process. This issue was especially apparent in efforts to write about the cyclic, iterative process that often occurs with improvement interventions.…”
Section: Squire 20 Developmental Pathmentioning
confidence: 99%
“…19 Semistructured interviews and focus groups with 29 end-users of SQUIRE 1.0 revealed that many found SQUIRE 1.0 helpful in planning and doing improvement work, but less so in the writing process. This issue was especially apparent in efforts to write about the cyclic, iterative process that often occurs with improvement interventions.…”
Section: Squire 20 Developmental Pathmentioning
confidence: 99%
“…In the evaluation of SQUIRE 1.0 19 and in the pilot testing, 22 many were perplexed by this item and its sub-elements. This item was intended to encourage a more formal assessment of the intervention and its associated outcomes.…”
Section: Studying the Intervention(s)mentioning
confidence: 99%
“…In the evaluation of SQUIRE 1.0 19 and in the pilot testing, 22 many were perplexed by this item and its sub-elements. This item was intended to encourage a more formal assessment of the intervention and its associated outcomes.…”
Section: Studying the Intervention(s)mentioning
confidence: 99%